2019
DOI: 10.5761/atcs.oa.18-00087
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Del Nido and Intermittent Warm Blood Cardioplegia in Coronary Artery Bypass Grafting Surgery

Abstract: Del Nido cardioplegia was developed for immature heart and pediatric surgery. But in our opinion, it is a good and useful alternative to CABG surgery with similar results to IWBC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 22 publications
1
39
0
Order By: Relevance
“…Administration of cold blood cardioplegia solution every 20 min increases the volume of cardioplegia solution. In the study performed by Ucak et al, in patients who underwent coronary bypass by using del Nido cardioplegia solution and blood cardioplegia solution, the cross clamp time and total CPB durations were shorter, and total volume of cardioplegia solution was less in del Nido cardioplegia solution, similar to our study [24]. In our study, there was no statistically significant difference between the groups in terms of intraoperative defibrillation requirement, LCOS, postoperative AF, postoperative kidney failure, intensive care stay and hospitalisation.…”
Section: Discussionsupporting
confidence: 90%
“…Administration of cold blood cardioplegia solution every 20 min increases the volume of cardioplegia solution. In the study performed by Ucak et al, in patients who underwent coronary bypass by using del Nido cardioplegia solution and blood cardioplegia solution, the cross clamp time and total CPB durations were shorter, and total volume of cardioplegia solution was less in del Nido cardioplegia solution, similar to our study [24]. In our study, there was no statistically significant difference between the groups in terms of intraoperative defibrillation requirement, LCOS, postoperative AF, postoperative kidney failure, intensive care stay and hospitalisation.…”
Section: Discussionsupporting
confidence: 90%
“…Two recently published Randomized Controlled Trials (RCT) compared the use of the DNC to the intermittent whole blood cardioplegia in CABG or CABG plus valve surgery. Ucak et al [25] could observe shorter aortic cross-clamp and CPBP times and better glucose control in the DNC group, without meaningful clinical differences in a population with an average Euroscore of 4.1. Similarly, Ad et al [26] conducted the single registered RCT (NCT02442050) for the DNC in adults.…”
Section: Experiences In Adult Patientsmentioning
confidence: 94%
“…CPB, X-clamp time Complication rates Inotropic support Need defibrillation UCAK et al . [25] CABG elective DNC = 112 IWBC =185…”
Section: Deliver and Technical Aspectsmentioning
confidence: 99%
“…13,14 O'Blenes et al 15 reported that the use of DN solution prevented spontaneous calcium -induced hypercontraction during cardiac arrest, reduced troponin release, and provided superior myocardial protection in isolated The ACC and CPB times were longer in patients undergoing surgery with DN cardioplegia, which is in contrast to previously published trials. 10,11 This was expected due to the inclusion of longer surgeries (valve and combined operations) in our trial, most of which were performed with DN cardioplegia. Compared with CB cardioplegia, patients receiving DN cardioplegia demonstrated higher postoperative troponin T levels, likely as a result of longer ACC and CPB times.…”
mentioning
confidence: 99%
“…In the majority of cardiac surgeries, a single application should be sufficient. 10 Importantly, less frequent dosing allows an uninterrupted surgery. logistic regression was adjusted for the propensity score for DN cardioplegia.…”
mentioning
confidence: 99%